Nidanatmaka (Epidemiological) Study in Patients Suffering From Impairment of Dhee Dhriti Smriti w.s.r. to Mild Cognitive Impairment - Sharma, Anshu; Sharma, Surendra Kumar; Gavali, Preeti (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: In Ayurveda Dhee means intelligence, Ability to correct judgement, Discriminative power etc Dhriti means–Self-control, patience, will power. Smriti means recalling the past experience or retention of memory. Aim: Present study was intended to assess the causative factor of dhee dhriti smriti vibhransha. Methods: A Nidanatmaka study was conducted at NIA Jaipur in which 500 subjects of both sex and age above 18 years were included after informed consent and the data were collected to assess the causative factors of dhee dhriti smriti vibhransha. Results: Virudha Ahara, vidahi usana tiksna ahara, puti paryusit bhojan,dusta ,ashuchi , ruksha ahara katu amla lavana rasa,chinta, shoka, moha,kama, krodha,lobha,irshya bhav are important nidana of manas roga in the current Nidanatmaka survey. Discussion: In this study it was concluded that there nidana, the foremost component of Nidana Panchaka, not only gives the knowledge of causative factors of a disease but also helps in treatment by avoiding them. Acharya Shushrut mentioned that Nidana Parivarjana (avoidance of causative factors) is the basis of Cikitsa. Since, the prevention of occurrence of disease is simple rather than treating the patient after developing disease.